Insurers' hidden risk from reinsurance recaptures. (9th September 2022) - Ugono, Mudi; Ashton, Brad; Brauch, Nora; Drew, Adél; Funnell, Jamie; Healey, Martin; Notani, Raj
Abstract: There is a lack of publicly available information covering the practices insurers employ to manage their exposure to reinsurance recapture risk. A working party was set-up to shed light on the different approaches insurers use to mitigate this complicated to manage risk. This report is intended to form part of a publicly available information repository that market practitioners can refer to and reflect on as best practice evolves and develops.